The Ethics of Intimacy: Understanding Hadith in the Context of Marital Rights and Rape Allegations - Muhammad Fiqih Cholidi; Ikhwan Ansori; Atssania Zahroh; Sholekhawati (UIN Syarif Hidayatullah Jakarta, 2025)
A superficial comprehension of hadith that depends exclusively on the text may hide the profound message conveyed by the Prophet. This research seeks to investigate the influence of culture on the interpretation of hadith and how academics contextualize it to reconcile the disparities in comprehension between rural and urban groups. The employed methodology is qualitative, utilizing a hermeneutic approach to hadith texts and a contextual examination of public reception. The study's findings indicate that a holistic approach, integrating textual and contextual meanings, might enhance the egalitarian ethos in Islam and render hadith more pertinent to modern social dynamics. Consequently, the significance of hadith is not merely normative but also capable of adapting to the cultural realities of society.